2021
DOI: 10.1016/j.healun.2021.04.003
|View full text |Cite
|
Sign up to set email alerts
|

BNT162b2 vaccination in heart transplant recipients: Clinical experience and antibody response

Abstract: Data on the safety and efficacy of SARS-CoV-2 vaccines in immunocompromised populations are sparse. We conducted a prospective study of 77 heart transplant (HT) recipients vaccinated with two doses of BNT162b2 vaccine and monitored for adverse events following both doses, the receptor-binding domain (RBD) IgG response, and neutralizing antibodies. BNT162b2 vaccination was associated with a low rate of adverse events, characterized mostly by pain at the injection site. By a mean 41 days post second dose there w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
140
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 119 publications
(159 citation statements)
references
References 9 publications
15
140
4
Order By: Relevance
“…Compared with previously published data on the seropositivity rate after vaccination of other immunosuppressed populations, such as patients who received heart or renal transplantation, the seropositivity rate of patients with cancer in our study was higher (18–37.5% vs 84%, respectively) [ [15] , 16 , 17 , 18 ].…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…Compared with previously published data on the seropositivity rate after vaccination of other immunosuppressed populations, such as patients who received heart or renal transplantation, the seropositivity rate of patients with cancer in our study was higher (18–37.5% vs 84%, respectively) [ [15] , 16 , 17 , 18 ].…”
Section: Discussioncontrasting
confidence: 86%
“…[ 14 ]. Data regarding safety and efficacy of mRNA COVID-19 vaccines in patients who were immune-compromised [ [15] , 16 , 17 , 18 ] and oncology patients [ [19] , 20 , 21 , [22] , 23 ] are now beginning to emerge.…”
Section: Introductionmentioning
confidence: 99%
“…Our finding of an association of immune paresis with the use of mycophenolate expend on the previously reported correlations following the second dose, 2 , 3 but should be carefully interpreted before any clinical actions carried out, given the potential hazardous implications associated with withdrawal of antimetabolite therapy. 3 The enhanced immune response demonstrated in our study following the third booster dose and the association with lower mycophenolate use might shed light on the previously observed more robust immune response in lung transplant patients after COVID-19 in contrast to the minimal response following vaccination.…”
Section: Discussionsupporting
confidence: 54%
“…In the general population, 1 the two-dose protocol for SARS-CoV-2 mRNA vaccines has been shown to elicit an excellent antibody response, but in SOT recipients antibody responses after 2 doses are markedly attenuated. 2 , 3 This attenuated antibody response translates into a clinical picture that includes breakthrough infections in fully vaccinated (2 doses) transplant recipients, 4 with the disease course being comparable to that in non-vaccinated SOT recipients. 5…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, studies have experimentally shown that serum from vaccinated individuals is less efficient in neutralizing viral variants [17,18]. On the other hand, post-vaccination infection may occur if vaccineinduced immunity is absent or ineffective, such as in solid organ transplant (SOT) recipients who are receiving immunosuppressive therapy [19][20][21][22][23][24]. Here we describe the characteristics of fourteen SARS-CoV-2 infections in fully vaccinated individuals at our medical center between 29 March 2021 and 29 April 2021 that represent both of these scenarios.…”
Section: Introductionmentioning
confidence: 99%